2004
DOI: 10.1523/jneurosci.1961-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Topographic, and Functional Organization of the Cerebellar Cortex: A Study with Combined Aldolase C and Olivocerebellar Labeling

Abstract: Aldolase C (zebrin) expression in Purkinje cells reveals stripe-shaped compartments in the cerebellar cortex. However, it is not clear how these compartments are related to cerebellar functional localization. Therefore, we identified olivocerebellar projections to aldolase C compartments by labeling climbing fibers with biotinylated dextran injected into various small areas within the inferior olive in rats. Specific rostral and caudal aldolase C compartments were linked in an orderly manner by common olivocer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
457
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(496 citation statements)
references
References 53 publications
33
457
6
Order By: Relevance
“…Specifically, the regional variation in synchrony loss (Fig. 5), combined with the fact that climbing fiber projections to crus 2a arise from multiple IO regions (Buisseret-Delmas and Angaut, 1993;Sugihara and Shinoda, 2004), suggest that diffusion barriers were a major reason for the incomplete loss of synchrony. Another factor is that carbenoxolone does not completely block electrical coupling (Rozental et al, 2001), as confirmed by the climbing fiber reflex results.…”
Section: Gap Junction Coupling Between Io Neurons Mediates Cs Synchronymentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the regional variation in synchrony loss (Fig. 5), combined with the fact that climbing fiber projections to crus 2a arise from multiple IO regions (Buisseret-Delmas and Angaut, 1993;Sugihara and Shinoda, 2004), suggest that diffusion barriers were a major reason for the incomplete loss of synchrony. Another factor is that carbenoxolone does not completely block electrical coupling (Rozental et al, 2001), as confirmed by the climbing fiber reflex results.…”
Section: Gap Junction Coupling Between Io Neurons Mediates Cs Synchronymentioning
confidence: 99%
“…To test this possibility, we made use of the fact that each region of the rat IO projects to a narrow rostrocaudally oriented strip of cortex (Buisseret-Delmas and Angaut, 1993;Sugihara and Shinoda, 2004), which corresponds to approximately two to three columns of cells in the recording array. Because we did not know the actual borders of the projection zones, we used a sliding window of three columns (Fig.…”
Section: Intercell Variation Of the Effect Of Carbenoxolone On Cs Synmentioning
confidence: 99%
“…Seven aldolase C-positive (1ϩ to 7ϩ) and -negative (1Ϫ to 7Ϫ) compartments are known to exist in each hemicerebellum (Brochu et al, 1990). PCs in each aldolase C compartment receive projections from neurons located in specific subnuclei of the inferior olive (Sugihara and Shinoda, 2004). PCs in each aldolase C compartment in turn project to a distinct subdivision of the deep cerebellar nuclei (Sugihara, 2011), which sends inhibitory projections back to the inferior olive (de Zeeuw et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Neurons from specific parts of the inferior olive send their climbing fibers to narrow, longitudinally arranged, strips of Purkinje cells (Voogd and Glickstein, 1998;Sugihara and Shinoda, 2004). These strips of Purkinje cells project to specific regions of the cerebellar nuclei that also receive direct input from collaterals of the same climbing fibers, thus resulting in a modular arrangement of olivo-cortico-nuclear connections (Pijpers et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the figures, roman numerals indicate individual lobules, and arrows are used to indicate their apices. The zebrin-positive bands are presented in gray, and the numbers and letters in these bands refer to the zebrinpositive compartments as defined by Hawkes and Leclerc (1987) and modified by Voogd and Ruigrok (2004) and by Sugihara and Shinoda (2004). The corresponding negative bands are positioned directly lateral to the positive bands.…”
Section: Introductionmentioning
confidence: 99%